Enhanced selectivity to olefins in the hydrodechlorination of trichloromethane using Ag-Pd on activated carbon catalysts. Issue 1 (February 2021) - Fernandez-Ruiz, C.; Liu, S.; Bedia, J.; Rodriguez, J.J.; Gómez-Sainero, L.M.
Graphical abstract: Highlights: High selectivity to olefins in trichloromethane hydrodechlorination with Ag-Pd carbon catalysts. PdCl2 as Pd precursor gives better results in terms of selectivity than Pd(NO3 )2 . The Pd particle size and oxidation state rule out the selectivity of the reaction. Outstanding 75 % selectivity to olefins and very high stability at 350 °C for 35 h. Abstract: Two Ag-Pd (nominal 1 % wt each) bimetallic catalysts supported on commercial activated carbon were synthesized and tested, for the first time, in the hydrodechlorination (HDC) of trichloromethane (TCM) to obtain light olefins. Two different Pd precursors were used, PdCl2 and Pd(NO3 )2, being the resulting catalysts denoted as AgPdCl/C and AgPdN/C, respectively. A monometallic Ag catalyst was also prepared for comparison purposes. The two different Pd precursors led to different metal particle sizes and zerovalent to electrodeficient metal ratios. The monometallic Ag catalyst showed a poor dechlorination, in contrast with the bimetallic ones. AgPdN/C yielded high selectivity to paraffins, while AgPdCl/C was more selective to olefins (mostly ethylene), the desired reaction products. This better behavior of AgPdCl/C in terms of selectivity to ethylene and propylene was probably due to the existence of smaller Pd nanoparticles as monometallic sites. These Pd sites are active for the conversion of chloromethanes into light unsaturated hydrocarbons, while larger Pd clusters present higher hydrogenation ability. AgPdCl/C allowed complete TCM conversion, with high overall dechlorination and outstanding 75 % selectivity to olefins, showing very high stability at a reaction temperature of 350 °C for almost 35 h on stream. These results represent a significant improvement respect to those obtained with monometallic Pd on activated carbon catalysts reported in our previous studies. To the best of our knowledge, for the first time it is reported such high selectivity to olefins as the above indicated from HDC of a chloromethane.